Dynamics of iron metabolism in patients with bloodstream infections: a time-course clinical study - Hiroshi Moro; Yuuki Bamba; Kei Nagano; Mariko Hakamata; Hideyuki Ogata; Satoshi Shibata; Hiromi Cho; Nobumasa Aoki; Mizuho Sato; Yasuyoshi Ohshima; Satoshi Watanabe; Toshiyuki Koya; et al. (Scientific Reports, 2023)
Abstract The close relationship between infectious diseases and iron metabolism is well known, but a more detailed understanding based on current knowledge may provide new insights into the diagnosis and treatment of infectious diseases, considering the growing threat of antibiotic-resistant bacteria. This study investigated adult patients with bloodstream infections, temporal changes, and relationships between blood levels of iron and related markers, including hepcidin and lipocalin-2 (LCN2). We included 144 samples from 48 patients (mean age 72 years, 50% male), with 30 diagnosed with sepsis. During the acute phase of infection, blood levels of hepcidin and LCN2 increased rapidly, whereas iron levels decreased, with values in 95.8% of cases below the normal range (40–188 μg/dL). Later, hepcidin and LCN2 decreased significantly during the recovery phase, and the decreased iron concentrations were restored. In the case of persistent inflammation, iron remained decreased. Acute LCN2 levels were significantly higher in patients with sepsis (p < 0.01). Hypoferremia induced by increased hepcidin would reduce iron in the environment of extracellular pathogens, and the increased LCN2 would inhibit siderophores, resulting in the prevention of the pathogen’s iron acquisition in each manner during the acute phase of bloodstream infection.